2021
DOI: 10.1302/1863-2548.15.200246
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of avascular necrosis following a cohort of treated developmental dysplasia of the hip in a single tertiary centre

Abstract: Purpose Avascular necrosis (AVN) may occur following treatment for developmental dysplasia of the hip (DDH). The primary aim of this study was to identify the incidence of AVN in a cohort of patients treated for DDH. Secondary aims were to classify AVN using available classification systems, analyze the correlation between the systems and investigate their relationship with the age at diagnosis of DDH. Methods An 11-year retrospective study was carried out at a single tertiary centre, using data from the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…This can only be achieved with a concentrically reduced hip. In a logistic regression analysis where they analyzed the effect of age at initial treatment on the development of AVN, they reported that their model predicted 83.9% accurately and the probability of AVN development was higher in those with advanced age at initial treatment (13). Achieving successful results gets harder as patients get older (4,8,14).…”
Section: Discussionmentioning
confidence: 99%
“…This can only be achieved with a concentrically reduced hip. In a logistic regression analysis where they analyzed the effect of age at initial treatment on the development of AVN, they reported that their model predicted 83.9% accurately and the probability of AVN development was higher in those with advanced age at initial treatment (13). Achieving successful results gets harder as patients get older (4,8,14).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hurley et al performed logistic regression on 250 hips treated with closed reduction only and found a significantly higher incidence of additional surgical intervention in patients who undergo treatment after 12 months of age [14]. Similarly, a retrospective study by Hussain et al reported a higher incidence of AVN in children who were diagnosed with DDH at an older age [28].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a retrospective study by Hussain et al . reported a higher incidence of AVN in children who were diagnosed with DDH at an older age [28].…”
Section: Discussionmentioning
confidence: 99%
“…The Smith Petersen approach is considered a safe approach in arthrogryposis-related dislocated hips even if done prior to the age of 12 months [ 10 ]. The AVN rate may reach 23% among patients who undergo open reduction of a dislocated hip [ 11 ]. Hip dislocation in arthrogryposis patients requires an extensive surgical approach due to the nature of the extensive fibrosis surrounding the capsule, which makes the reduction difficult and increases the risk of complications, including redislocation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%